KNOWLEDGE ON HYPOGLYCEMIA AMONG PATIENTS WITH DIABETES MELLITUS. - P, Thenmozhi; M, Vijayalakshmi (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The objective of the study is to assess the level of knowledge on hypoglycemia among patients with diabetes mellitus in the rural community. Hypoglycemia is an acute complication of diabetes mellitus. The recognition of hypoglycemia and immediate treatment of hypoglycemia should be known by all the diabetic patients so that treatment of hypoglycemia may not be delayed, need for hospitalization could be avoided, and life-threatening complications due to hypoglycemia may be prevented. Methods: A cross-sectional research design was adopted with 60 samples who met the inclusion criteria in the rural community in India. Structured interview method was used to collect the data. Data were analyzed by descriptive and inferential statistics. Result: Of 60 samples, 38 (63.33%) had inadequate knowledge, 12 (20%) of them had moderately adequate knowledge, and 10 (16.67%) of them had adequate knowledge. There is a significant association between the age and type of treatment at the level of p<0.05 with the level of knowledge on hypoglycemia. Conclusion: The study findings emphasized that majority of the patients with diabetes mellitus do not have the knowledge on hypoglycemia. The health-care professional has an important role in educating diabetics on hypoglycemia so that hypoglycemic episodes and morbidity could be reduced or prevented.